Kritik Ekologi dalam Buku Kumpulan Puisi Selepas Musim Menjauh Karya Ahmad Sultoni - Fadila, Diana; Israhayu, Eko Sri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This research aims to describe the forms of ecological criticism in the poetry collection Selepas Musim Menjauh by Ahmad Sultoni. This type of research is qualitative descriptive research with a literary ecology approach. This research data is in the form of words, sentences, phrases, or paragraphs that contain a form of ecological criticism. The data collection technique used in this research is the reading and note taking technique. The findings in this research show five forms of ecological criticism in the poetry collection book Selepas Musim Menjauh by Ahmad Sultoni, including: (1) criticism of land conversion, (2) criticism of environmental pollution, (3) criticism of climate change, (4) criticism of natural use, and (5) criticism of natural disasters. In this research, critical data on climate change is the most dominant. There are several titles that contain criticism of climate change, including: (a) Hari yang Tak Bermusim, (b) Kampung Halaman, (c) Suara Burung yang Murung, (d) Berjalan ke Barat Kembali ke Timur, (e) Desa-desa yang Tak Lagi Berkisah, (f) Tempat yang Dirahasiakan, and (g) Kamus Baru. Through ecological criticism it can be seen that the poet has sensitivity to environmental problems that arise around the poet. This can make readers aware that there are many environmental problems around the reader. It is hoped that readers can maintain the balance of nature, use nature wisely, and preserve nature for life in the future.Key words: ecological criticism, poetry, literature